LINGUISTIC METHODS IN LEARNING LEGAL TERMS (Proceedings of International Educators Conference, 2024)
This article talks about the need to choose words when composing a legal text, to distinguish the necessary word from the list of words with other meanings, to choose words according to the type of speech, to whom the speech is addressed, and the purpose of the speech. An opinion was expressed on the fact that the terms differ from common words by some of their own characteristics, the specific signs of the terms, and the impossibility of using synonyms or doublets in the system of terms of the same network.